APPLICATION OF VALIDATED RP-HPLC METHOD FOR THE DETERMINATION OF ARMODAFINIL IN BULK AND FORMULATION - Ramesh, Devi; Habibuddin, Mohammad (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of the present study is to develop and validate a simple, rapid, sensitive reverse phase HPLC method for the determination of Armodafinil present in bulk and its pharmaceutical formulations. Methods: The chromatographic separation was achieved by using Hypersil ODS C-18 (150 x 4.6 mm, 5Âµ) in an isocratic mode with mobile phase methanol: phosphate buffer 3.0 (60:40 %v/v) was used. The flow rate was 1 ml/min and effluent was monitored at 225 nm. The method was validated for validation parameters i.e. linearity, accuracy, precision and robustness according to ICH guidelines. Results: The retention time of Armodafinil was 4.2 min and the linearity range of the method was 500-20000ng/ml with regression (r2) coefficient 0.9998. The method was validated for precision, accuracy, robustness and which were found to be within the acceptable limits according to the ICH guidelines. Also, the method was successfully applied for the estimation of Armodafinil in the marketed formulation of Nuvigil and the recovery was found to be>98%. Conclusion: The developed method possess good selectivity, specificity, there is no interference found in the blank at a retention time of ARM and good correlation between the peak area and concentration of the drugs under prescribed conditions. Hence, the method can be applied for routine analysis of Armodafinil. Â